We need scientific minds as role models for youth - Abd Razak, Dzulkifli (2008)
UNIVERSITI Sains Malaysia started the New Year with a bang, when our angkasawan negara descended on the campus on Jan 5. Like the space launch itself, it was a historic moment not only for USM. About 5,000 came out in support, including about 1,500 following the event in lecture halls through closecircuit television cameras. The facetoface encounter with Dr Sheikh Muszaphar Shukor (SMS, for short) proved an encounter of a lifetime. For almost 1 1/2 hours, they were mesmerised by the detailed experiences that Dr Muszaphar shared with them, beginning with his childhood ambition to venture into space 25 years ago up to his tumultuous entry back to Earth.